Silsesquioxane organofunctionalized with 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole: preparation and subsequent reaction with silver and potassium hexacyanoferrate(III) for detection of l-cysteine - Carmo, Devaney R. do[UNESP]; Silvestrini, Daniela R. [UNESP]; Silveira, Tayla F. S. de [UNESP]; Cumba, Loanda R. [UNESP]; Dias Filho, Newton L. [UNESP]; Soares, Layciane A. [UNESP] (Elsevier B. V., 2015)
The octakis(3-chloropropyl)octasilsesquioxane (SS) was organofunctionalized with 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole (Purpald). The functionalized silsesquioxane with Purpald (SP) was characterized by Fourier transform infrared spectroscopy (FT-IR), and nuclear magnetic resonance (NMR). After functionalized, silsesquioxane can interact with silver nitrate and subsequently with potassium hexacyanoferrate (III) (AgHSP). The novel hybrid composite formed (AgHSP) was characterized by Fourier transform infrared spectra, scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDX). AgHSP was electrochemically characterized by cyclic voltammetry (CV) using graphite paste electrode. The AgHSP incorporated into a graphite paste electrode (20% w/w) was tested for detection of l-cysteine. The modified electrode showed a linear response from 9.0×10(-5) to 5.0×10(-3)molL(-1) with the corresponding equation Y(A)=0.01315+1.865 [l-cysteine], and a correlation coefficient of r(2)=0.9995. The method showed a detection limit of 1.76×10(-4)molL(-1) with a relative standard deviation of ±2% (n=3) and amperometric sensitivity of 1.865A/molL(-1).
Keywords: Chemical synthesis; Electrochemical properties; Infrared spectroscopy; Nuclear magnetic resonance (nmr); Structural materials